A dictionary and grammatical sketch of Ruruuli-Lunyala (Volume 5) - Namyalo, Saudah (Language Science Press, 2021)
This book is a dictionary and grammar sketch of Ruruuli-Lunyala, a Great Lakes Bantu language spoken by over 200,000 people in central Uganda. The dictionary part includes about 10,000 entries. Each lexical entry provides translations into English, example sentences, and basic grammatical information. The dictionary part is supplemented with an outline of the Ruruuli-Lunyala grammar, which treats most of the phonological and morpho-syntactic topics. This book is a result of a joined effort of a large team of linguists and many speakers of Ruruuli-Lunyala and is intended as a resource for linguists and Ruruuli-Lunyala speakers, learners, and educators.